Representasi Feminisme dalam Episode 1 'Jeng Yah' dari Serial 'Gadis Kretek': Sebuah Analisis Semiotik - Zulvi Kori’ah; Al Husain, A. Hasan; Gracia, Amanda Bunga (JOM, 2024)
This research aims to analyze the representation of gender roles in the character "Jeng Yah" from the Kretek Girl film series, focusing on the interplay of reality, representation, and ideology. The study responds to the significant shifts brought about by the modern feminist movement, which has motivated many women to engage in feminist activism and pursue higher education. Employing John Fiske's semiotic analysis, this qualitative research examines three dimensions: reality, representation, and ideology, as portrayed in the Kretek Girl series. The analysis of the first episode yields three primary findings: (1) At the reality level, the film employs various codes—appearance, movement, expression, conversation, and behavior—to construct gender roles. (2) At the representation level, the film utilizes camera work, lighting, and music to visually and aurally reinforce the narrative's meanings. (3) At the ideological level, the character Jeng Yah embodies feminist ideals as she seeks personal liberation. The study concludes that the use of signs and codes in the film serves to convey feminist ideologies, with visual and narrative elements contributing significantly to this ideological expression. Ultimately, the research suggests that the film encourages women to comprehend and incorporate feminist principles into their everyday lives.